Balancing Challenges and Opportunities: Enhancing Early Childhood Cognitive Skills Through Digital Tools - Loka, Novita; Sabila, Rizky Thania (GENIUS: Indonesian Journal of Early Childhood Education, 2024)
This study investigates the role of digital tools, particularly educational videos, in enhancing early childhood cognitive skills at Pertiwi Indralaya Kindergarten. Using a qualitative descriptive approach based on the Miles and Huberman framework, data were collected through classroom observations, interviews, and documentation involving 20 children aged 4–5. Findings reveal that 55% of students exhibited "Very Well Developed" cognitive skills, while 45% were "Developing as Expected," with no children in lower categories. Key cognitive areas improved included problem-solving, memory retention, and logical reasoning, supported by a balanced integration of digital and traditional learning methods. Challenges such as maintaining focus and avoiding screen dependency underscore the need for structured guidance. The study concludes that combining digital and conventional strategies can foster cognitive development, highlighting the importance of teacher facilitation and responsible technology use in early childhood education.